Simulation Environment Conceptual Design for Life-Saving UAV Flights in Mountainous Terrain - Natália Gecejová; Marek Češkovič; Pavol Kurdel (Drones)
The civil and military use of autonomously or remotely controlled unmanned aerial vehicles (UAVs) has become standard in many sectors. However, their role as supplementary vehicles for helicopter emergency medical services (HEMS) or search and rescue (SAR)—particularly when aiding individuals in hard-to-reach terrains—remains underexplored and in need of further innovation. The feasibility of using UAVs in such operations depends on multiple factors, including legislative, economic, and market conditions. However, the most critical considerations are external factors that impact UAV flight, such as meteorological conditions (wind speed and direction), the designated operational area, the proficiency of the pilot–operator, and the classification and certification of the UAV, particularly if it has been modified for such missions. Additionally, the feasibility of the remote or autonomous control of the UAV in mountainous environments plays a crucial role in determining their effectiveness. Establishing a specialized simulation environment to address these challenges is essential for assessing UAV performance in mountainous regions. This is particularly relevant in the Slovak Republic, a very rugged landscape, where the planned expansion of UAV-assisted rescue operations must be preceded by thorough testing, flight verification, and operational planning within protected landscape areas. Moreover, significant legislative changes will be required, which can only be implemented after the comprehensive testing of UAV operations in these specific mountain environments.